Patients' Perceptions of Corrective Experiences in Naturalistically Delivered Psychotherapy. Issue 2 (23rd November 2016) - Constantino, Michael J.; Morrison, Nicholas R.; Coyne, Alice E.; Goodwin, Brien J.; Santorelli, Gennarina D.; Angus, Lynne
Abstract : Corrective experiences (CEs), which suggest transformative experience(s) for the psychotherapy patient, have a rich theoretical history; yet there is little empirical information on patients' own perceptions of what gets "corrected" from therapy, and what is "corrective" (i.e., the mechanisms driving the CE). To address this gap, we investigated 14 patients' posttreatment accounts of both CE elements in the context of naturalistically delivered individual psychotherapy, using a consensual qualitative research methodology. Extending prior research focused on patients' accounts of CEs while still engaged in treatment (Heatherington et al., 2012), the present results revealed that patients retrospectively identified an array of categories that were deemed corrected, such as positive changes in cognitions, interpersonal problems, self‐concepts, symptoms, and behaviors. Patients also identified CEs that may have led to those shifts/transformations, including their therapist's actions (especially giving feedback), their own agentic actions (especially engaging in the therapeutic process), and the patient–therapist collaborative and engaged relationship. Clinical practice implications are discussed.